2006
DOI: 10.1093/treephys/26.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic regulation in leaves and roots of olive trees during a water deficit and rewatering

Abstract: We evaluated the osmotic adjustment capacity of leaves and roots of young olive (Olea europaea L.) trees during a period of water deficit and subsequent rewatering. The trials were carried out in Basilicata (40 degrees 24' N, 16 degrees 48' E) on 2-year-old self-rooted olive plants (cv. 'Coratina'). Plants were subjected to one of four drought treatments. After 13 days of drought, plants reached mean predawn leaf water potentials of -0.45 +/- 0.015 MPa (control), -1.65 +/- 0.021 (low stress), -3.25 +/- 0.035 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 35 publications
6
76
0
3
Order By: Relevance
“…Nevertheless, some species of plants can absorb water soil at a potential much smaller than this limit. For example olive trees can set a water potential gradient between dry soil (-3 MPa) and leaf (-7 MPa) (Dichio et al, 2006). Similarly, Larrea divaricata may absorb water at -6.0 MPa soil water potential (Kirkham, 2005).…”
Section: Soil Watermentioning
confidence: 99%
“…Nevertheless, some species of plants can absorb water soil at a potential much smaller than this limit. For example olive trees can set a water potential gradient between dry soil (-3 MPa) and leaf (-7 MPa) (Dichio et al, 2006). Similarly, Larrea divaricata may absorb water at -6.0 MPa soil water potential (Kirkham, 2005).…”
Section: Soil Watermentioning
confidence: 99%
“…Drought stress in Citrus reduced stomatal conductance, leaf transpiration rate, and net CO 2 assimilation rate ). Furthermore, Dichio et al (2006) reported that stomatal conductance and net photosynthetic rate declined with increasing drought stress. Water stress induced a decrease in the quantum yield of PSII electron transport of wheat plants (Triticum aestivum L.), suggesting that water stress resulted in modifications in PSII photochemistry (Lu and Zhang, 1999).…”
Section: Leaf Water Potential -Photosynthetic Ratementioning
confidence: 99%
“…At cellular level, osmotic adjustment is an adaptive mechanism in which the accumulation of solutes helps to maintain a favourable gradient of water potential in the soil-plant-air system. It allows to maintain a sufficient water absorption from a relatively dry soil for sustaining photosynthetic and transpiration activity, and cell expansion for root growth (Mastrangelo et al, 2011a;Dichio et al, 2006). Regarding the importance of this trait in improving grain yield in water stressed environment, a positive correlation between osmotic adjustment and yield increases has been found in particular in conditions of severe water stress (Serraj & Sinclair, 2002).…”
Section: Morpho-physiological Traits Involved In the Response To Watementioning
confidence: 99%